The Principal's Strategy in Improving Madrasah Teacher Performance - Syaifuddin; Moh. Rofiki (Managere: Indonesian Journal of Educational Management, 2025)
The performance of teachers in madrasahs plays a crucial role in the overall quality of education. This study explores the principals' strategies in improving teacher performance at madrasahs, with a particular focus on the leadership approach and pedagogical collaboration methods. The research utilizes a qualitative approach, including interviews and observations of the strategies implemented by school principals. The findings reveal that active leadership based on example, regular structured pedagogical collaboration, and an emphasis on professional development are key factors in enhancing teacher performance. Additionally, the study highlights the importance of fostering a collaborative environment where teachers engage in continuous learning and teamwork. The role of principals in setting clear expectations, providing support, and facilitating opportunities for professional growth is found to be essential in creating a motivated and effective teaching staff. The study concludes that effective leadership and strategic collaboration are critical to improving teacher performance in madrasahs, ultimately contributing to the overall quality of education.